Basis and applicability of noninvasive inverse electrocardiography: a comparison between cardiac source models - Jeanne van der Waal; Veronique Meijborg; Ruben Coronel; Rémi Dubois; Thom Oostendorp (Frontiers in Physiology, 2023)
The body surface electrocardiogram (ECG) is a direct result of electrical activity generated by the myocardium. Using the body surface ECGs to reconstruct cardiac electrical activity is called the inverse problem of electrocardiography. The method to solve the inverse problem depends on the chosen cardiac source model to describe cardiac electrical activity. In this paper, we describe the theoretical basis of two inverse methods based on the most commonly used cardiac source models: the epicardial potential model and the equivalent dipole layer model. We discuss similarities and differences in applicability, strengths and weaknesses and sketch a road towards improved inverse solutions by targeted use, sequential application or a combination of the two methods.